ANALYSIS OF WORK CLIMATE AND ORGANIZATIONAL CULTURE ON TEACHER PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENTING VARIABLEAT SMP NEGERI 1 PINTU RIME GAYO BENER MERIAH REGENCY - Zulman; Mesra B; Sri Rahayu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines the influence of work climate and organizational culture on teacher performance, with job satisfaction acting as an intervening variable. The research was conducted at SMP Negeri 1 Pintu Rime Gayo, Bener Meriah Regency, using a quantitative approach. Data was collected from a saturated sample of 81 teachers (ASN and PPPK) through questionnaires. The results of SmartPLS analysis indicate that work climate has a direct and significant positive effect on both teacher performance and job satisfaction. Organizational culture has a significant positive effect on job satisfaction, but not directly on teacher performance. Furthermore, job satisfaction has a positive and significant impact on teacher performance. Finally, both work climate and organizational culture positively and significantly influence teacher performance through job satisfaction. The study suggests the importance of improving work climate, organizational culture, and job satisfaction to enhance teacher performance.